PsycEXTRA Dataset 2011
DOI: 10.1037/e512592013-284
|View full text |Cite
|
Sign up to set email alerts
|

Time causes forgetting from working memory

Abstract: Although forgetting in the short term is a ubiquitous phenomenon, its exact causes remain undecided. The aim of the present study was to test the temporal decay hypothesis according to which memory traces fade away with time when attention is diverted by concurrent activities. In two experiments involving complex span tasks, adults were asked to remember series of items (either letters or spatial locations) while verifying multiplications. The duration of processing was manipulated by presenting multiplication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
1
3
0
1
Order By: Relevance
“…The unique contribution of processing speed is consistent with models of working memory span performance in which individual or developmental differences in processing efficiency lead to variation in the time during which maintenance activities are prevented and forgetting can occur (i.e., Barrouillet et al, 2004Barrouillet et al, , 2007Barrouillet et al, , 2009Barrouillet et al, , 2012Bayliss et al, 2005; see also Towse et al, 1998). Likewise, the unique contribution of storage ability is consistent with models in which individual or developmental differences in reactivation rate determine the amount of information that can be successfully maintained or refreshed in any unoccupied time windows that occur during the working memory span task Bayliss et al, 2005).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The unique contribution of processing speed is consistent with models of working memory span performance in which individual or developmental differences in processing efficiency lead to variation in the time during which maintenance activities are prevented and forgetting can occur (i.e., Barrouillet et al, 2004Barrouillet et al, , 2007Barrouillet et al, , 2009Barrouillet et al, , 2012Bayliss et al, 2005; see also Towse et al, 1998). Likewise, the unique contribution of storage ability is consistent with models in which individual or developmental differences in reactivation rate determine the amount of information that can be successfully maintained or refreshed in any unoccupied time windows that occur during the working memory span task Bayliss et al, 2005).…”
Section: Discussionsupporting
confidence: 76%
“…As a consequence of this, the speed with which individuals complete the processing operations leads to variation in the time during which forgetting can occur whilst maintenance activities are prevented. Evidence to support this suggestion comes from a recent study by Barrouillet et al (2012), who showed that lengthening the duration of the processing activity whilst maintaining a constant time between the end of each processing activity and presentation of the subsequent storage item (i.e., the time available for restoring or refreshing the memory trace) resulted in poorer memory performance, consistent with the idea that longer processing leads to greater forgetting (see also, Bayliss et al, 2005, who showed that age-related changes in a speed of processing variable accounted for unique variance in working memory span performance). In addition, by systematically manipulating the amount of time during which children were engaged in processing and the time they had available for refreshing memory items, Barrouillet et al (2009) were able to show that the slope relating the time available for refreshing memory items with working memory span performance was steeper in older relative to younger children.…”
Section: Memory Span Performancementioning
confidence: 91%
See 1 more Smart Citation
“…La troisième hypothèse est que les traces mémorielles sur lesquelles l'attention se concentre reç oivent de l'activation, mais, dès que l'attention est déplacée, cette activation souffre d'une dégrada-tion liée au temps Barrouillet, Portrat, Vergauwe, Diependaele, & Camos, 2011 ;Barrouillet, De Paepe, & Langerock, 2012 ;Cowan, 1995Cowan, , 1999Portrat, Barrouillet, & Camos, 2008 ;Towse & Hitch, 1995). Par conséquent, dans les tâches d'empan complexe mais aussi dans le fonctionnement de la mémoire de travail en général, les traces mnésiques doivent être activement maintenues avant de disparaître lorsque l'attention est occupée par un traitement.…”
Section: Le Modèle De Partage Temporel Des Ressourcesunclassified
“…Altmann, 2009;Barrouillet, De Paepe, & Langerock, 2012;Cowan & AuBuchon, 2008;Lewandowsky, Duncan, & Brown, 2004;Lewandowsky, Oberauer, & Brown, 2009;Neath & Nairne, 1995;. Barrouillet, Portrat, Vergauwe, Diependaele, andCamos (2011, p. 1315) have stated that "there is no direct evidence against the hypothesis of a time-related decay in the short-term", but other researchers have been much more critical and favour interference as the cause of forgetting (e.g.…”
Section: Introductionmentioning
confidence: 99%